ANTIDIABETIC EFFECT TEST OF CENTELLA ASIATICA EXTRACT IN HYPERCHOLESTEROLEMIA RAT MODELS - Nafiisah, Nafiisah; Aini Gumilas, Nur Signa; Harini, Ika Murti (JURNAL WIDYA MEDIKA, 2024)
Introduction: High blood sugar levels can lead to hypercholesterolemia, a condition where cholesterol levels in the blood exceed normal values. The active compounds in Centella asiatica (pegagan) have the potential to act as antidiabetic agents by stimulating insulin production by pancreatic beta cells. Objective: This study aims to determine the effect of Centella asiatica extract on lowering fasting blood glucose (FBG) levels in hypercholesterolemia rat models. Methods: Thirty-two test animals were divided into 4 groups: normal control, negative control, positive control (Simvastatin 1.8 mg/kgBW/day), and treatment (Centella asiatica extract 500 mg/kgBW/day). Hypercholesterolemia was induced using 2% cholesterol and 0.2% cholic acid. FBG measurement was performed after 5 weeks of administration of Centella asiatica extract and Simvastatin. Data analysis used one-way ANOVA and post hoc Bonferroni tests. Results: The mean FBG (mg/dL) in P1=70.85±1.89; P2=151.82±2.91; P3=92.34±1.86; and P4=83.89±2.17. The one-way ANOVA test results showed statistically significant differences (p